Pls. provide explanations. Thanks : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 16 Jan 2017, 02:53

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Pls. provide explanations. Thanks

 post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
Manager
Joined: 01 Feb 2006
Posts: 78
Location: New York
Followers: 1

Kudos [?]: 1 [0], given: 0

Pls. provide explanations. Thanks [#permalink]

### Show Tags

06 Dec 2006, 07:41
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Pls. provide explanations. Thanks
Attachments

gmatprep_19.doc [67.5 KiB]

Senior Manager
Joined: 19 Jul 2006
Posts: 361
Followers: 2

Kudos [?]: 6 [0], given: 0

### Show Tags

06 Dec 2006, 09:18
C

Both statement alone is not sufficient
but on subtracting (2) from (1) we get s= 3r +2 which proves (r,s) lies on y=3x +2
Manager
Joined: 01 Feb 2006
Posts: 78
Location: New York
Followers: 1

Kudos [?]: 1 [0], given: 0

### Show Tags

06 Dec 2006, 09:26
AK wrote:
C

Both statement alone is not sufficient
but on subtracting (2) from (1) we get s= 3r +2 which proves (r,s) lies on y=3x +2

Can you elaborate a little bit more?

From (1), I get s = 3r + 2 or s = 4r + 9
From (2), I get s = 4r - 6 or s = 3r + 2

When we combine 1 & 2 , we get s = 3r + 2. Is this what you meant ?
Senior Manager
Joined: 19 Jul 2006
Posts: 361
Followers: 2

Kudos [?]: 6 [0], given: 0

### Show Tags

06 Dec 2006, 09:47
from (1)
(3r+2 -s)(4r +9 -s)= 0
on expanding it, we get

12*r^2 + s^2 - 7rs +35r - 11s + 18 = 0 ..... (a)

similarly expanding (2), we get

12*r^2 + s^2 - 7rs - 10 r +4s -12 = 0 ......(b)

now a - b will give

45*r - 15*s + 30 = 0

0r, s= 3r +2

given equation of line y= 3x+2

so we can say (r,s) lies on the line
Manager
Joined: 01 Feb 2006
Posts: 78
Location: New York
Followers: 1

Kudos [?]: 1 [0], given: 0

### Show Tags

06 Dec 2006, 10:04
AK wrote:
from (1)
(3r+2 -s)(4r +9 -s)= 0
on expanding it, we get

12*r^2 + s^2 - 7rs +35r - 11s + 18 = 0 ..... (a)

similarly expanding (2), we get

12*r^2 + s^2 - 7rs - 10 r +4s -12 = 0 ......(b)

now a - b will give

45*r - 15*s + 30 = 0

0r, s= 3r +2

given equation of line y= 3x+2

so we can say (r,s) lies on the line

Thanks, AK. Does my method above seem plausible?
Senior Manager
Joined: 19 Jul 2006
Posts: 361
Followers: 2

Kudos [?]: 6 [0], given: 0

### Show Tags

06 Dec 2006, 10:16
sujayb wrote:
AK wrote:
C

Both statement alone is not sufficient
but on subtracting (2) from (1) we get s= 3r +2 which proves (r,s) lies on y=3x +2

Can you elaborate a little bit more?

From (1), I get s = 3r + 2 or s = 4r + 9
From (2), I get s = 4r - 6 or s = 3r + 2

When we combine 1 & 2 , we get s = 3r + 2. Is this what you meant ?

Your method is convincing ... this is the fastest way to solve
06 Dec 2006, 10:16
Display posts from previous: Sort by

# Pls. provide explanations. Thanks

 post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.